2020
DOI: 10.1108/sr-11-2019-0259
|View full text |Cite
|
Sign up to set email alerts
|

Element sensor based on microplasma generators

Abstract: Purpose The purpose of this paper is to present a study on miniaturized instruments for analytical chemistry with a microplasma as the excitation source. Design/methodology/approach The atmospheric pressure glow microdischarge could be ignited inside a ceramic structure between a solid anode and a liquid cathode. As a result of the cathode sputtering of the solution, it was possible to determine its chemical composition by analyzing the emission spectra of the discharge. Cathodes with microfluidic channels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The most promising results were obtained for the drop system, the application of which has many advantages, such as no microfluidic pumps, discharge stability and no liquid waste. Preliminary studies have been reported in [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The most promising results were obtained for the drop system, the application of which has many advantages, such as no microfluidic pumps, discharge stability and no liquid waste. Preliminary studies have been reported in [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of LTCC to fabricate multilayer circuits opens this technology to microsystem technology (MST), which is applied in the production of various sensors [ 5 ]. The LTCC has already been used for fabrication of plasma generators [ 5 , 6 , 7 , 8 ] for s elements in liquidous solutions [ 6 , 7 , 8 , 9 ] or flowing gas [ 10 ].…”
Section: Introductionmentioning
confidence: 99%